2022
DOI: 10.1186/s12889-022-13409-0
|View full text |Cite
|
Sign up to set email alerts
|

Social media use and mental health during the COVID-19 pandemic in young adults: a meta-analysis of 14 cross-sectional studies

Abstract: Background Public isolated due to the early quarantine regarding coronavirus disease 2019 (COVID-19) increasingly used more social media platforms. Contradictory claims regarding the effect of social media use on mental health needs to be resolved. The purpose of the study was to summarise the association between the time spent on social media platform during the COVID-19 quarantine and mental health outcomes (i.e., anxiety and depression). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 26 publications
(21 reference statements)
3
27
1
Order By: Relevance
“…According to this literature review, the influence of SM use on the MH of adolescents and students during the COVID-19 pandemic has been significant. The findings of this review indicate that SM use was predominantly associated with the mental ill-being of adolescents and students during the early months of the COVID-19 pandemic [ 21 , 22 , 23 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], most commonly related to MH problems, such as depression, anxiety and stress [ 21 , 22 , 23 , 24 , 27 , 28 , 29 , 31 , 32 ], which is in line with recent publications regarding SM use and its influence on MH of the younger population during the COVID-19 pandemic [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 83%
“…According to this literature review, the influence of SM use on the MH of adolescents and students during the COVID-19 pandemic has been significant. The findings of this review indicate that SM use was predominantly associated with the mental ill-being of adolescents and students during the early months of the COVID-19 pandemic [ 21 , 22 , 23 , 24 , 25 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], most commonly related to MH problems, such as depression, anxiety and stress [ 21 , 22 , 23 , 24 , 27 , 28 , 29 , 31 , 32 ], which is in line with recent publications regarding SM use and its influence on MH of the younger population during the COVID-19 pandemic [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionsupporting
confidence: 83%
“…When we further compared mental health and health-related quality of life indicators among the students with their different usage times for SNSs, the results showed that the students who spent from <1 h to ~2–3 h per day using SNSs reported lower levels of depression, anxiety, and stress than did the students who spent more than 3 h on SNSs per day, while the group of students who never used SNSs had a level of negative emotions that was comparable with that of the group with more than 3 h daily on SNSs. Contrary to other recent findings showing that the increase in the time spent using SNSs was associated with anxiety problems during the pandemic [see the meta-analysis by Lee et al ( 57 )], our findings suggest that using SNSs for 3 h per day or somewhat less can have beneficial effects on adolescents' mental health during the pandemic. The SNSs can provide a convenient and safe channel for youths to use for communicating and connecting with their peers, families, and teachers when face-to-face interaction is restricted; SNSs also give adolescents access to the most updated information with reference to their studies, life, health, and the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…However, other studies reported a detrimental association, by outlining that COVID-19-related restrictive measures and lockdown favored an excessive SM use and increased the risk of developing a PSMU [39,[69][70][71]. Indeed, a recent metanalysis collecting data coming from 14 cross-sectional studies carried out during the COVID-19 pandemic among young people in different countries, reported that an excessive time spent on social networking platforms was much more likely associated with an increased risk of developing depressive (OR = 1.43) and anxiety symptoms (OR = 1.55) [72].…”
Section: Discussionmentioning
confidence: 99%